DIPLOMASI INDONESIA TERHADAP ORGANISASI KERJA SAMA ISLAM (OKI) DALAM MENANGANI KONFLIK ROHINGYA - Dio Rofi Sanyoto, Setyasih Harini, GPH Dipokusumo (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2019)
ABSTRACTThis research described and analyzed diplomacy conducted by Indonesia Governmentconcerning Organization of Islamic Cooperation in dealing with Rohingya conflict. RohingyaConflict formerly constituting a Myanmar’s internal state conflict goes global. It was becausethe effect was felt not only by Myanmar or corresponding ethnic but also felt by Myanmar’sneighbor states including Indonesia. As the state affected by the conflict, Indonesia tooksome attempts to deal with Rohingya Conflict. Out of some attempts taken by Indonesia,there was a multilateral diplomatic taken by Indonesia concerning international organization.One of those international organizations was Islam-based International Organization,Organization of Islamic Cooperation. The author employed Multilateral Diplomacy withHuman Right approach. The objective of research was to find out what diplomatic attemptIndonesia had taken on Organization of Islamic Cooperation in dealing with RohingyaConflict. The research method employed in this study was qualitative research one withprimary and secondary data. Data collection was conducted using interview anddocumentation methods and the data collected was analyzed descriptively.. From the data of research, the author found that diplomatic attempts Indonesia had takenagainst Organization of Islamic Cooperation had not been maximal due to some constraints.Keywords: Multilateral Diplomacy, Republic of Indonesia Government, Organization ofIslamic Cooperation, Myanmar Government